Perinatal outcome in babies born through meconium stained liquor in Shree Birendra Hospital - Bajiko, Nirjana; Suwal, Allen; Dhital, Kapil Raj (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Meconium stained amniotic fluid has long been considered to be a bad predictor of fetal outcome. Presence of meconium in amniotic fluid is a potentially serious sign of fetal compromise and is associated with poor perinatal outcomes. This study was undertaken to find out the perinatal outcomes in babies born through meconium stained liquor at Shree Birendra hospital.Method: This was a prospective cross sectional study conducted in department of obstetrics and gynecology of Shree Birendra Hospital over a period of 1 year, from 1st Mar 2019 to 30th of Feb 2020. A total of 68 pregnant women in labor after 37 completed weeks with singleton pregnancy with cephalic presentation with meconium stained amniotic fluid were enrolled in this study after taking detailed history and performing complete examination.Result: Incidence of thin meconium staining was 7(10.3%) cases; moderate meconium 44(64.7%) and thick meconium 17(25%). Out of 68 cases, intrauterine fetal heart rate abnormalities were observed in 32(47.1%). Fortyeight (70.58%) mothers with meconium stained liquor underwent cesarean section. Low APGAR scores were more common in neonates born with thick meconium. Twenty-seven (39.70%) of total neonates born through meconium stained amniotic fluid required resuscitation. Neonates born through thick meconium required more invasive resuscitation. Similarly, signs of respiratory distress were more commonly seen in thick meconium group. Five (7.35%) of neonates were admitted in neonatal intensive care unit, in which 80% were from thick meconium group and 20% from moderate group. Three (4.41%) required mechanical ventilation; all of them were from thick group. Meconium aspiration syndrome was diagnosed in 1(1.47%) of total deliveries with frequency higher with thick meconium. Similarly, mortality rate was 1(1.47%) of total deliveries which included neonates from thick meconium group.Conclusion: Meconium stained amniotic fluid is associated with intrauterine fetal heart rate abnormalities and increased rates of caesarean deliveries. Low APGAR score is observed in neonates with thick MSL. The rate of NICU admission in neonates born through MSAF are mostly from thick MSAF group.